The Influence of School Climate on Teacher Performance in State High Schools at Manggala District, Makassar City - Novianti, A. Aulia Reski Novianti; Maisyaroh, Maisyaroh; Ahmad Yusuf Sobri (Education Specialist, 2023)
School climate is one of the factors that can influence teacher performance in carrying out their duties, because a conducive school climate has a positive influence on teachers in carrying out their duties. A good school climate will have a positive impact on teachers' teaching performance in learning at State High Schools in Manggala Regency. The research objectives were to find out (1) a description of the school climate in State High Schools in Manggala District; (2) description of the performance of State High School teachers in Manggala District; and (3) does the school climate influence the performance of State High School teachers in Manggala Regency. Data collection was carried out by distributing questionnaires and then processing it using the SPSS application, so this research is quantitative research. The population was 217 people, 140 people were used for sampling using the random sampling method. The research results show that (1) the description of the school climate is in the good category; (2) the description of teacher performance is in the good category; and (3) partially the school climate has a significant effect on teacher performance.